Experimental analysis of waste polyurethane from household appliances and its utilization possibilities - Stančin, Hrvoje; Růžičková, Jana; Mikulčić, Hrvoje; Raclavská, Helena; Kucbel, Marek; Wang, Xuebin; Duić, Neven (Journal of environmental management, 2019)
Polyurethane has a good insulation characteristic, and it is widely used as an insulation and lining material for refrigerators. Nevertheless, at the end of a product's lifetime, serious problems arise related to waste management. Recently, energy recovery has been marked as a promising solution, especially, waste-to-energy applications. To find an appropriate application for such waste, a thermal analysis was performed. An experimental analysis of polyurethane (PU) waste material was performed by the method of pyrolysis gas chromatography with mass spectrometric detection (Py-GC/MS) at various pyrolytic temperatures, namely, at 500, 600 and 700 °C. Waste polyurethane foam was conducted to investigations in the form of a bulk sample and sorted grain-size samples with a goal to detect the chemical composition of the pyrolysate. The investigation revealed various groups of organic compounds such as heterocyclic compounds of nitrogen and simple and polycyclic aromatic hydrocarbons, while notable concentrations of compounds containing chlorine were detected as well. The experimental analysis found differences in the composition of amines and other compounds and in the dependence on grain size composition. Bulk samples produced the highest concentration of amines (˃ 40%) at a temperature of 500 °C. The sample homogenization led to a significant increase in amines production. Polyurethane waste of grain size from 0.125 to 0.25 mm contained approximately 80% amines. The pyrolysis of the bulk sample at 600 °C yielded only 24% nitrogen heterocyclic compounds, while from the sorted grain-size <0.045 mm and 0.045-0.063 mm, yields were increased to 47.4 and 45.7%, respectively.
Keywords: Waste-to-energy; Gas Chromatography-Mass Spectrometry; Temperature; odpadní produkty; Pyrolysis; Waste Products; Pollutant emission; PAH; polycyklické aromatické uhlovodíky; teplota; plynová chromatografie s hmotnostně spektrometrickou detekcí; Polycyclic Aromatic Hydrocarbons; Polyurethanes; polyurethany; Polyurethane waste